PENGARUH SELF-EFICACY DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN CMB EXPEDISI DI SAMARINDA - Syaparliddin Syachrani; Eko Ravi Pratama; Irfan Yusuf; Dhika Nurul Fauzi (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
This study aims to analyze the influence of self-efficacy and job characteristics on organizational commitment and employee performance at CMB Expedisi in Samarinda. Employee performance is a critical factor in determining organizational success, particularly in the face of intense competition and increasing demands for excellent public service. Self-efficacy, which reflects an individual’s belief in their ability to successfully complete tasks, is believed to significantly impact both performance and organizational commitment. Additionally, job characteristics such as task variety, job significance, and work autonomy play a key role in shaping employee engagement with the organization. Organizational commitment is positioned as a mediating variable that connects self-efficacy and job characteristics with employee performance. Field observations reveal ongoing challenges such as low self-confidence, monotonous tasks, and underutilized feedback, all of which contribute to performance decline. This research is expected to contribute to human resource development strategies by enhancing self-efficacy, improving job design, and strengthening organizational commitment to drive optimal employee performance.